Developing ADDIE-Based Islamic Religious Education Learning Tools to Foster Spiritual Intelligence and Multicultural Empathy among Vocational High School Students - Andew iSuhartinia; Nur Sab'rina Fathimah; Qorie Hizratul Muttaqien; Ayub Suganda; Mugeni Muhammad; Achmad Nurdiansyah (At Turots: Jurnal Pendidikan Islam, 2026)
This research aims to develop Islamic Religious Education (PAI) learning tools for grade X students of SMK Negeri Cisarua using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model which is theoretically supported by Transformative Learning Theory, Spiritual Intelligence Development Framework, and Empathy-Based Learning. The development process involves the creation of teaching materials, learner worksheets, learning implementation plans, and assessment instruments designed to enhance a deep understanding of Islam, develop compassion for religious differences, and internalize universal spiritual values through reflective learning and contemplative practices. The results of the expert validation showed an average score of 85.3% content validity and 87.8% design validity (in the very valid category). The practicality test based on teacher and student responses reached 88.7% and 90.2% respectively (very practical category). Effectiveness testing through learning outcomes showed a significant improvement with an average pre-test score of 61.2 and post-test score of 84.1 (Cohen's d = 1.62, large effect size, p < 0.001), which attests to a substantial increase in knowledge of Islamic values and universal spiritual principles. Spiritual Intelligence experienced a significant increase (pre: 2.68, post: 4.12 on a scale of 5, Δ = 1.44, p < 0.001), consistent with the perspective transformation mechanism in Transformative Learning Theory. Empathy for religious minorities showed a significant increase (pre: 2.35, post: 3.97, Δ = 1.62, p < 0.001), reflecting the development of interfaith compassion even in the context of mono-religious schools. Conclusion: the PAI learning tools developed have proven to be valid, practical, and highly effective in simultaneously improving students' knowledge, transforming spiritual perspectives, and developing an empathetic attitude towards religious diversity in the context of Islamic education. The integration of Transformative Learning with the development of Spiritual Intelligence is an innovative contribution to the Islamic educational literature and the development of multicultural competencies in Indonesia.